Considerations of the Public Prosecutor in Filing Charges and Demands for the Defendant in Sexual Violence Cases against Individuals with Intellectual Disabilities - Salsabila, Feliza; Tongat, Tongat; Fajrin, Yaris Adhial (Universitas Muhammadiyah Malang, 2023)
In handling cases of sexual violence experienced by persons with intellectual disabilities, the Public Prosecutor must have great skills in understanding the laws and regulations that will be used in drafting charges in court. The purpose of this study is to examine the consideration of the Public Prosecutor in filing charges and charges in case number PDM– 020/Eku.2/BTM/01/2022. The research method used is a normative legal research method with a statutory approach and a conceptual approach. The results of the study show that First, the Public Prosecutor uses/determines the charges against the maker/sexual violence for persons with intellectual disabilities in case Number: PDM– 020/Eku.2/BTM/01/2022, based on objective factors and subjective factors. Objective factors refer to factors that relate to the rules of laws and regulations. Subjective factors are factors that are related or related to the perpetrator and criminal responsibility which he has carried out. Criminal liability. Second, the Public Prosecutor's claim in case Number PDM– 020/Eku.2/BTM/01/2022 is in accordance with the principle of legal certainty. However, the legal certainty provided by the Public Prosecutor does not necessarily provide benefits for victims with intellectual disabilities.